Implementation of Islamic Business Ethics in Digital Wallet: Literature Review Approach - Dhiyaul Aulia Zulni; Siti Achiria (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2019)
The wallet is concise because it has a concise form in managing the identity card or money owned by the wallet owner for transactions. Therefore, when someone does not bring his wallet, he will feel restless or uncomfortable because he does not bring his wallet so it is difficult when trying to make a transaction. Digital Wallet or commonly called Electronic Wallet (e-Wallet) is the latest economic phenomenon based on Information Technology that makes it easy for consumers to make transactions at merchants that have worked together. Digital Wallet Market in Indonesia continues to experience an increase in the number of users that have been proven at the end of 2018 in Indonesia, which has reached Rp 21 trillion. Indonesia has a majority population who embrace Islam. Therefore, in this study aims to examine how the practice of Digital Wallet using Islamic perspectives, especially from the view of business ethics. Based on the results of the literature study, the author seeks to provide examples of the implementation of Digital Wallet practices based on the axioms of Islamic business ethics consisting of 4 pillars of Islamic Business Ethics in general which include the concepts of Unity, Justice, Free Will, and Responsibility.